Comparative Analysis of Coastal Green Open Space Conversion and Its Environmental Consequences Across Coastal Districts of North Sumatra - Darwin Parlaungan Lubis; Sendi Permana; Bagus Setiabudi Wibowo; M Taufik Rahmadi; Dewi Permata Sari; Yessi Karolina Marbun (Jurnal Geografika (Geografi Lingkungan Lahan Basah), 2026)
This study examines the conversion of Coastal Green Open Space (CGOS) in the coastal areas of North Sumatra Province using a systematic literature review (SLR) approach based on PRISMA, synthesizing findings from 25 scientific articles. The results indicate that CGOS conversion is a complex and multidimensional phenomenon driven by the interaction of anthropogenic, biophysical, and governance factors. Three primary conversion patterns are identified: rapid conversion in industrial and port areas, gradual conversion in aquaculture and plantation zones, and ecological fragmentation in land–sea transition areas. The main driving factors include coastal urbanization, economic and industrial expansion, land use change, climate change pressures, and weak policy implementation. Among these, urbanization and economic growth emerge as the most dominant forces accelerating land conversion. The environmental consequences are systemic, including the decline of ecosystem services, increased coastal flooding and disaster risks, biodiversity degradation, hydrological disturbances, and reduced environmental quality due to the loss of coastal vegetation. Comparative analysis reveals significant spatial variation among coastal districts, where highly urbanized areas experience more rapid and intensive conversion, while aquaculture-based regions undergo gradual yet cumulative changes. These findings highlight that the sustainability of coastal ecosystems is highly dependent on the presence of CGOS as natural protection and ecological support systems. Therefore, integrated and ecosystem-based coastal management is essential, emphasizing spatial planning, green infrastructure development, technological monitoring, and community participation to ensure long-term sustainability.